Ser cidadão: leitura de textos normativos e análise da realidade escolar em aula de língua portuguesa no ensino fundamental II - Gabriela Vilela Andrade (2023)
When considering young people’s integral formation, the school environment needs to provide spaces for dialogue and interaction between students, teachers, administrators, and the school community. In other words, the student is not a passive subject who only receives and memorises finished content. To promote spaces that favour the engagement and political participation of young people, this work is a teaching project, therefore, a set of pedagogical activities of reading discursive genres from the legal sphere, and one of its goals is to “invite” the youth to identify their rights and duties as citizens and students, through the comparison of the law and regulations with their daily basis reality. The theoretical foundation is divided into three concepts, namely: a) the problematising school and the formation of the transforming teacher (FREIRE, 1979, 1996, 2013 e 2017; GIROUX, 1997; PARO, 2017); b) the language as a social interaction object, loaded with ideologies that contribute to the formation of citizens (BAKHTIN, 2003; STREET, 2020; ANTUNES, 2020); c) the legal language inaccessible to most people (SANTOS, 2014; SILVA PINTO, 2010; CARVALHO, 2021; COSTA E IANNI, 2018). From a methodological perspective, the teaching project comprises Portuguese classes from students’ interests and experiences. The project highlights the importance of reading to the citizenship exercise and proficiency in reading discursive genres of the legal sphere such as laws, documents, statutes, regulations, etc. Other goals of the teaching project are to teach the students to observe critically if the sayings of the legal sphere match their reality, to identify ombudsperson channels and government accountability, and to plan their arguments when claiming their rights before authorities. As a result, we hope to have better student participation, primarily in school decision-making and exercising their citizenship in a democratic country.